Energy efficiency of manufacturing supply chains: Swedish survey findings - Hilmola, Olli-Pekka; Fobbe, Lea; Haartman, Robin von; Hilletofth, Per (Frontiers in Energy Research, 2025)
Due to increasing emission reduction requirements and higher energy prices, manufacturing companies have started to pay attention to the energy efficiency of supply chains, instead of focusing solely on operations. As emission reduction and energy efficiency often share the same objectives, these are frequently addressed together in earlier research. The aim of this research is to examine, through a survey, the level of energy efficiency work conducted by manufacturers with suppliers, and the drivers behind such activities. Based on survey findings completed in 2024, Swedish manufacturers are taking initial steps in energy efficiency work along with suppliers. Typically, suppliers are asked to provide energy use information and analyses. Top management support is the most important driver for this work, followed by a company’s environmental profile, production cost reduction, and an emphasis on Scope 3 emission reduction. There is also some evidence that companies with the public sector as their main customer are more active in energy efficiency work with suppliers.